Houndsley and Catina and the birthday surprise - Howe, James, 1946-; Gay, Marie-Louise (Cambridge, Mass. : Candlewick Press, 2006)
Friends Houndsley and Catina are sad because they do not know when their birthdays are, but they solve the problem in a thoughtful and creative way.
A Junior Library Guild selection.
Keywords: Dogs -- Fiction; Cats -- Fiction; Birthdays -- Fiction; Parties -- Fiction; Friendship -- Fiction; Dogs -- Juvenile fiction; Cats -- Juvenile fiction; Birthdays -- Juvenile fiction; Parties -- Juvenile fiction; Friendship -- Juvenile fiction